A Companion to Early Modern Women's Writing. - Pacheco, Arturo (Blackwell companions to literature and culture., 2008)
This timely volume represents one of the first comprehensive, student-oriented guides to the under-published field of early modern women's writing.:.; Brings together more than twenty leading international scholars to provide the definitive survey volume to the field of early modern women's writing.; Examines individual texts, including works by Mary Sidney, Margaret Cavendish and Aphra Behn.; Explores the historical context and generic diversity of early modern women's writing, as well as the theoretical issues that underpin its study.; Provides a clear sense of the full extent of women's con.